Siglec15 Checkpoint Blockade for Simultaneous Immunochemotherapy and Osteolysis Inhibition in Lung Adenocarcinoma Spinal Metastasis via a Hollow Nanoplatform. Issue 29 (25th June 2022) - Liang, Haifeng; Zhou, Lei; Hu, Zhichao; Ge, Yuxiang; Zhang, Taiwei; Chen, Qing; Wang, Ben; Lu, Shunyi; Ding, Wang; Dong, Jian; Xue, Fengfeng; Jiang, Libo
Abstract: Low responsiveness to anti‐programmed death‐1/programmed death‐ligand 1 (anti‐PD‐1/PD‐L1) for solid tumors indicates the presence of other immunosuppressive pathways. Siglec15, a newly discovered immune checkpoint, has been reported to repress immune responses in the tumor microenvironment (TME) and regulate osteoclast differentiation. However, the role of Siglec15 in the treatment for bone metastasis remains unclear. Herein, Siglec15 shows significantly higher expression in lung adenocarcinoma spinal metastasis (LUAD‐SM) than in para‐cancerous spinal tissues and primary LUAD. Subsequently, a TME‐responsive hollow MnO2 nanoplatform (H‐M) loaded with Siglec15 siRNA and cisplatin (H‐M@siS15/Cis) is developed, and the surface is modified with an aspartic acid octapeptide (Asp 8 ), thus allowing H‐M to target spinal metastasis. High drug‐loading capacity, good biocompatibility, effective tumor accumulation, and efficient Siglec15 silencing are demonstrated. Furthermore, the nanoparticles could reverse immunosuppression caused by tumor cells and tumor‐associated macrophages (TAMs) and inhibit osteoclast differentiation via Siglec15 downregulation in vitro. In a LUAD‐SM mouse model, H‐M@siS15/Cis‐Asp 8 exhibits superior therapeutic efficacy via synergetic immunochemotherapy and osteolysis inhibition. Taken together, this single nanoplatform reveals the therapeutic potential of the new immune checkpoint Siglec15 in LUAD‐SM and provides a strategy to treat this disease. Abstract : According to the high expression of Siglec15 in lung adenocarcinoma spinal metastasis (LUAD‐SM), an actively targeted tumor microenvironment (TME)‐responsive hollow MnO2 nanoplatform is designed for enhanced synergetic immunochemotherapy and osteolysis inhibition via downregulation of Siglec15 in both tumor cells and tumor‐associated macrophages. Such a nanoplatform can provide a strategy for "killing two birds with one stone" to treat LUAD‐SM.